Minimally invasive intervention of forniceal rupture in a solitary functioning kidney: A case report - Abdulrahman Alharbi; Talha Saleem; Rehan Nasir Khan; Ahmed Farag; Abdullatif Al-Terki (Urology Case Reports)
Renal Forniceal rupture is a common urological emergency, most commonly due to an underlying ureteral obstruction. There is no standardized management for forniceal rupture. We report a 70-year-old female who presented with vague abdominal symptoms, and acute on Chronic Kidney Disease. Plain Computed Tomography scan of the abdomen/pelvis revealed grossly disturbed renal anatomy, with a large perinephric collection, and an obstructing pelvic-ureteric junction stone. She was initially managed with intravenous antibiotics, percutaneous drain and percutaneous nephrostomy placement. She subsequently underwent right flexible ureteroscopy and double-J stenting. Prompt, early intervention resulted in return of renal anatomy and facilitated early recovery.